The Elements of Brand Anthropomorphism: Qualitative Investigation Into Local Brands Amongst Young Adult Consumers - Mayasari, Iin; Haryanto, Handrix C (UI Scholars Hub, 2022)
Manuscript type: Research Article Research Aims: This study aimed to describe the elements of brand anthropomorphism and self-brand congruity based on the review of Guido and Peluso's conceptualization. Design/methodology/approach: This study collected the data from generation Y respondents through semi-structured depth interviewing. Research Findings: The critical finding provides the context of Asian consumers related to local brands. Emerging local brands can grow if the organization can manage them well. Theoretical Contribution/Originality: It describes the elements of brand anthropomorphism associated with the domain of consumer-brand relationships among Asian consumers. Practitioner/Policy Implication: The local brands should be perceived that all brands are not similar in the same category. Research limitation/Implications: The elements of brand anthropomorphism can create brand personality. Keywords: Brand anthropomorphism, brand congruity, brand personality.